Analysis of Prototyping Methods Implementation for Library Information Systems Development in SMAN 3 Bengkalis - Anggy Trisnadoli; Devi Yanti (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2022)
SMAN 3 Bengkalis Library is a school library with a collection of reading books and lessons located in Bengkalis Regency, Riau Province. Currently, the system that operates in the SMAN 3 Bengkalis library is still conventional and is prone to physical damage. In addition, with current technological advances, the registration system for students as members is also still written using paper cards, plus the difficulties of library staff in procuring and managing library books. Based on these problems, a web-based library information system development is proposed, expected to solve the problems that occur. With prospective system users who are pretty laymen, a particular way is needed to develop the system, especially when carrying out user needs and system design. With this need, a prototyping method is used, which does function to accommodate these needs. Each phase of this method is carried out carefully to produce a product that meets expectations. In this study, an evaluation of the development process was carried out. The evaluation is carried out in several ways, such as UAT and Usability Testing with ISO 9126 and 9241-111. Based on the results of the evaluation, it was found that with the application of this method can produce a library information system product that is good and runs according to functionality and is to the expectations of users in solving the problems they face.